2008
DOI: 10.1128/jvi.00949-08
|View full text |Cite
|
Sign up to set email alerts
|

Subviral Particle Release Determinants of Prototype Foamy Virus

Abstract: Glycoproteins of several viruses have the capacity to induce release of noninfectious, capsidless particulate structures containing only the viral glycoprotein. Such structures are often called subviral particles (SVP). Foamy viruses (FVs), a special type of retroviruses with a replication strategy combining features of both orthoretroviruses and hepadnaviruses, express a glycoprotein (Env) which has the ability to induce SVP release. However, unlike human hepatitis B virus, prototype FV (PFV) naturally secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Protein samples from cellular lysates or purified particulate material were separated by SDS-PAGE on a 10% polyacrylamide gel and analyzed by immunoblotting as described previously [98]. Polyclonal rabbit antisera specific for PFV Gag [99] or residues1 to 86 of the PFV Env leader peptide (LP), [98] as well as hybridoma supernatants specific for PFV PR-RT (clone 15E10) or PFV integrase (IN) (clone 3E11) [100] were employed. After incubation with species-matched horseradish peroxidase (HRP)-conjugated secondary antibody, the blots were developed with Immobilon Western HRP substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Protein samples from cellular lysates or purified particulate material were separated by SDS-PAGE on a 10% polyacrylamide gel and analyzed by immunoblotting as described previously [98]. Polyclonal rabbit antisera specific for PFV Gag [99] or residues1 to 86 of the PFV Env leader peptide (LP), [98] as well as hybridoma supernatants specific for PFV PR-RT (clone 15E10) or PFV integrase (IN) (clone 3E11) [100] were employed. After incubation with species-matched horseradish peroxidase (HRP)-conjugated secondary antibody, the blots were developed with Immobilon Western HRP substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal antisera used were specific for PFV Gag [54] or the LP of PFV Env, aa 1 to 86 [53]. The chemiluminescence signal was digitally recorded using a LAS-3000 imager.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the well-known degradation process induction ubiquitination in PFV therefore exhibits a second function in the context of viral egress and infectivity. More recent analysis by the same group revealed that only the first two lysine residues are important with regard to ubiquitination and suppress SVP release to wild type levels [81]. As FV-Env is, in contrast to all other retroviruses capable of budding independent of any other FV protein, this mechanism might tightly regulate SVP release, at least in PFV.…”
Section: Molecular Biology Of Fvmentioning
confidence: 99%